(untitled) (Research, Society and Development, 2022)
Objective: The objective was to characterize the profile of patients with pressure injuries who were admitted to hospital units of Clinical Medicine and Neurology. Methodology: This is a documentary retrospective, quantitative and descriptive analysis study, carried out in the Clinical Medicine and Neurology units of a teaching hospital in the interior of Minas Gerais. The collection of data, in 27 medical records, was performed using a form, containing the demographic and clinical characteristics of the patients, from August to September 2020. Results: Among the main results, the following stand out: 85.2 % of patients were admitted to the medical clinic; 55.6% female; with an average age of 67 years. Pressure injuries were more prevalent in the sacral region (63.0%), and 33.3% were in stage II of evolution. Conclusion: By knowing the characteristics of patients with pressure injuries, it is possible to provide the scientific basis for decision making.